The effect of refugia on prey-predator model with parasite infection - Fitri Nur Azizah; Annisa Risda Alivia; Habban Riawan Syahrul Haz; Ubaidullah Yashkun (International Journal of Applied Mathematics, Sciences, and Technology for National Defense, 2024)
This study examines the impact of prey-hiding behavior on predator-prey dynamics within theoretical and mathematical ecology. We conduct both analytical and numerical analyses to explore the effects of protection on these dynamics. Our model divides the prey population into two subclasses: susceptible prey (S(t)) and infected prey (I(t)), changing over time. Utilizing a Holling's model type-1, we find that the trivial equilibrium of the model is unstable, while both the disease-free and disease equilibrium points are stable. These simulations provide insights into the characteristics of animals in natural environments.